AKTIVITAS ANTIHIPERURISEMIA INFUSA DAUN KENIKIR (Cosmos caudatus Kunth.) PADA MODEL MENCIT HIPERURISEMIA TERINDUKSI KALIUM OKSONAT - Erwin Samsul; Muhammad Romi Adipasa Pratama; Baso Didik Hikmawan; Herman Herman; Junaidin Junaidin; Lizma Febrina; Arsyik Ibrahim; Rolan Rusli; Hifdzur Rashif Rijai; Islamudin Ahmad; Arman Rusman; M. Arifuddin (Jurnal Farmasi Medica/Pharmacy Medical Journal (PMJ), 2026)
Hyperuricemia is a metabolic disorder characterized by elevated serum uric acid levels due to excessive production or impaired excretion. Conventional therapy using xanthine oxidase inhibitors such as allopurinol is effective but may cause adverse effects with prolonged use. This study aimed to evaluate the antihyperuricemic activity of kenikir (Cosmos caudatus Kunth.) leaf infusion in a potassium oxonate-induced hyperuricemic mouse model. Phytochemical screening revealed the presence of alkaloids, flavonoids, saponins, and tannins. Twenty-five male mice were randomly assigned into five groups (n=5): negative control (0.5% NaCMC), positive control (allopurinol 100 mg/kgBW), and three treatment groups receiving 10%, 15%, and 20% infusion. Hyperuricemia was induced using chicken liver juice and potassium oxonate (300 mg/kgBW). Each mouse received 0.5 mL orally. Blood uric acid levels were measured hourly for four hours using EasyTouch GCU. Statistical analysis using the Kruskal–Wallis test showed no significant difference among groups (p=0.220). However, descriptively, the 15% concentration demonstrated the highest percentage reduction (56.77%), followed by 20% (41.28%) and 10% (38.74%), compared with allopurinol (66.01%). These findings suggest that kenikir leaf infusion exhibits potential antihyperuricemic activity and supports further investigation with optimized dosing, larger sample size, and enzymatic validation. Keywords: Cosmos caudatus, hyperuricemia, potassium oxonate, uric acid